(untitled) (Journal of International Studies, 2018)
Cooperation in the humanitarian sphere is one of the priorities in the activities of the Shanghai Cooperation Organization (SCO). Over the years of the existence of the SCO, the countries that belong to it, have established practical and effective cooperation in the fields of culture, education, environmental protection, youth policy, sports, tourism and media. As the SCO is adding its members, this form of interaction starts playing an increasingly important role. The SCO countries have certain achievements in developing various aspects of humanitarian cooperation. Student, teacher and academic staff exchange projects are being realized, direct contacts between educational institutes have been established; languages, history, culture, and literature of the SCO member states are being studied. Multilateral mechanism of interaction has been formed — meetings of the ministers of education of the SCO member states; a permanent expert group, which coordinates joint efforts in this area, has been created.